Managing and evaluating projects - Alleyne, Frank (Arawak Pub. KingstonJM, 2003)
Examines the multifaceted project management in the Commonwealth Caribbean countries in such sectors as the public service, agriculture, research and development, industry, infrastructure, education, health, housing, performance, and policy planning and integration. Demonstrates project monitoring and evaluation and project performance via field research.